2008
DOI: 10.1007/s10643-007-0233-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Mentor-coaching Model on Teacher Professional Development

Abstract: The purpose of this study was to examine the impact of the mentor-coach initiative model on participating Head Start Programs. The researchers interviewed 44 participants across two mid-western states. The participants provided positive feedback about the initiative and identified specific literacy practices based on this model that were successfully implemented in their classrooms. Evidence from this study suggests the importance of incorporating the mentor-coaching initiative model to enhance teacher pedagog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 8 publications
0
34
0
2
Order By: Relevance
“…The researchers concluded that the 2 hour training was effective in increasing teacher use of math mediated language, but they recommend following up with the coaching model as this is where the largest increase in teacher use of math mediated language was observed. Onchwari and Keengwe (2008) used a qualitative method to examine the effects of a mentor-coach initiative model on literacy in Head Start programs. They conducted one-on-one interviews that resulted in a number of themes.…”
Section: Research On Side-by-side Coachingmentioning
confidence: 99%
“…The researchers concluded that the 2 hour training was effective in increasing teacher use of math mediated language, but they recommend following up with the coaching model as this is where the largest increase in teacher use of math mediated language was observed. Onchwari and Keengwe (2008) used a qualitative method to examine the effects of a mentor-coach initiative model on literacy in Head Start programs. They conducted one-on-one interviews that resulted in a number of themes.…”
Section: Research On Side-by-side Coachingmentioning
confidence: 99%
“…While planning the process, the teacher-researcher and the coach collaborated to determine the goals and relevant competence areas on which to focus during the professional development process. In line with these findings, planning and determining goals during coaching, and pursuing the process via concrete and systematic steps are said to be significant in terms of monitoring whether goals are attained or not (Jovanova-Mitkovska, 2010;Onchwari & Keengwe, 2008). On the other hand, the relevant literature also underlines that the teacher should not only be a willing participant but also be aware of his/her professional development needs for coaching based professional development to be successful (Lowenhaupt et al, 2013;Rhodes & Beneicke, 2002).…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, Li and Chan (2015) studied a coaching based professional development program that they found to have a high influence on professional development. The results of several other studies examining coaching yielded that the process not only had positive effects on teachers' professional development but also increased students' literacy skills and verbal language development (Barkley, 2005;Onchwari & Keengwe, 2008). A number of other studies focusing on coaching special education teachers have also been identified as a result of the literature review.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Müfettişler ders denetimi yapmadıkları için öğretmenlerle birebir iletişim kuramadıklarını ve bu yüzden de öğretmenlere yönelik rehberlik ve iş başında yetiştirme görevini yerine getiremediklerini düşünmektedirler. Oysaki yapılan birçok çalışmada öğretmenlerin hizmet içi eğitimlerinin mesleki gelişimleri için hayati önem taşıdığı ortaya konmuştur (Hany & Lumpe, 1995;Onchwari & Keengwe, 2008). Ancak mesleki gelişimin okul başarısı üzerindeki etkisi göz önünde bulundurulmadan hizmet içi eğitim faaliyetleri kemer sıkma politikalarının kurbanı haline gelmesinden dolayı (Bredson & Johansson, 2006) bahsedilen mesleki gelişimin okullarda gerçekleşmesi bir zorunluluk haline gelmiştir.…”
Section: Sonuç Tartışma Ve öNerilerunclassified